Analysis of Naratological Structure in Raditya Dika's Hangout Film - Maknun, Lulu'il (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
This study aims to describe the narrative structure of Raditya Dika's Hangout using naratology theory. Hangout is a film with elements of thriller and mystery. This research is the basis for naratological studies because the theory that researchers use there is a discussion of narrative structure which includes story, plot, time and space. This narrative structure is the basis of naratology which will be developed again into several parts according to the data obtained. The data obtained in this study was sourced from the film Hangout by Raditya Dika which lasted 110 minutes and was released in 2016. The type of research data used by researchers is qualitative data. To obtain qualitative data, researchers collected data which was described through three components, namely a literature review to multiply references and find relevant information, observations by watching Hangout movies and recording by focusing on Hangout movie scenes. The analysis of this research was carried out by collecting related data which was described through these three components and developed. This research seeks to understand and find a more detailed description of the storyline. Based on the results of the analysis, it was obtained that in analyzing the storyline in the film, it is necessary to understand each series of events and the connected arrangement of elements that are interrelated systematically or in accordance with applicable regulations. Therefore, to understand the storyline in the Hangout film, you must understand the narrative structure contained in the film so that the story can be understood properly.